South African teachers learning to become writers and writing teachers: A study of generative learning. (May 2016) - Assaf, Lori Czop; Ralfe, Liz; Steinbach, Beth
Abstract: In this qualitative case study, we examine South African teachers' generative learning after participating in a professional development project focused on writing and describe how the teachers enacted writing instruction in their classrooms six months after the project. Building on generative change theories, we explored how teachers used free writing to become metacognitive of their writerly identities and create time and space for their students to do the same. The teachers shifted in their beliefs and understanding of different writing discourses and the importance of using themselves and culturally relevant texts to mediate their students' writing. Graphical abstract: Highlights: Teachers' writerly identities mediated students' learning. Teachers' written texts mediated students' writing. Teachers developed additive views of students, enhancing their confidence and agency. Generative model of professional development supported teacher identities.